Assessment of Bactrocera dorsalis (Diptera: Tephritidae) Diets on Adult Fecundity and Larval Development: Insights Into Employing the Sterile Insect Technique. Issue 1 (12th January 2020) - Hou, Qiu-Li; Chen, Er-Hu; Dou, Wei; Wang, Jin-Jun
Abstract: Bactrocera dorsalis (Hendel) is a notorious insect pest that attacks diverse vegetables and fruits worldwide. The sterile insect technique has been developed as an environmentally friendly and effective control method that depends on the mass production of target flies. Because dietary yeast (protein) and sucrose (carbohydrate) are important in adult diets, yeast:sucrose (Y:S) mixtures are crucial for the mass-rearing of B. dorsalis . In this study, we found adult diets with different ratios of yeast to sucrose-influenced fecundity, and an extremely high or low Y:S ratios significantly decreased egg production of B. dorsalis . Additionally, the maximum oviposition efficiency was realized at dietary yeast to sucrose ratios of 1:1 and 1:3, suggesting their potential use to produce more eggs for the mass production of B. dorsalis . Here, new gel diets having different yeast concentrations (g/L water) were also assessed for rearing B. dorsalis larvae. Gel diets containing 20 g/L yeast led to a higher pupation, pupal weight and adult eclosion rate, and a shorter developmental time than other yeast concentrations. Moreover, the present gel diet also resulted in greater pupal production and adult emergence rates than previously used liquid and solid artificial diets, revealing that it is suitable for rearing B. dorsalis larvae. This research provides a useful reference on artificial diets mixtures for mass rearing B. dorsalis, which is critical for employing the sterile insect technique.